Mental Distress and Pseudo-Hagiography in Hrafns saga Sveinbjarnarsonar - Van Deusen, Natalie M. (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2026)
This article examines Hrafns saga Sveinbjarnarsonar as a significant yet overlooked source for understanding constructions of mental distress in medieval Iceland. Although the saga is a categorized as one of the samtíðarsögur (contemporary sagas), its depiction of two individuals cured by Hrafn closely parallels treatments and terminology in Icelandic hagiography. Through these episodes, the saga presents mental impairment as intertwined with physical symptoms and treatable through Hrafn’s combined medical skill and divinely bestowed healing powers. Their clear resemblance to miracle accounts strengthens the classification of the saga as pseudo-hagiographic, a characterization further supported by the omission of these scenes in the Sturlunga saga version. These examples contribute to broader discussions of disability, healing, and sanctity in medieval Icelandic literature.